Microwave-assisted rapid conjugation of horseradish peroxidase-dextran aldehyde with Schiff base reaction and decolorization of Reactive Blue 19 - Celeb, Mithat; Ozdemir, Zafer Omer; Topuzogullari, Murat (Tubitak Scientific & Technological Research Council Turkey, 2022)
Microwave irradiation has become a routine technique in homogeneous and effective heating in organic synthesis. However, its application in enzyme-containing reactions is limited since it can cause denaturation of the enzyme. In this study, we have briefly investigated the effect of microwave heating on the conjugation reaction of horseradish peroxidase (HRP) with aldehyde derivative of dextran (D-CHO). The reaction was irradiated by microwave at 50 degrees C for 5 min. The conjugate was confirmed via GPC, in which the conjugates of HRP and D-CHO coexist with free unbound HRP molecules. Activity studies of HRP revealed that there is a small decrease in conjugate activity relative to the free enzyme after a short bioconjugation reaction with microwave irradiation. In decolorization studies of the textile dye Reactive Blue 19 (RB19), 99% of RB19 was decolorized through the free enzyme at 35 degrees C while the decolorization of the dye was 96% at 25-35 degrees C by the conjugate, which is a critical result showing clearly that the HRP conjugated via D-CHO is not denatured and still active after microwave-assisted reaction. This phenomenon is due to the multiple point conjugation of D-CHO on the surface of HRP and locking the 3D structure which may prevent changes in the secondary or tertiary structure of the enzyme. The results reveal that microwave irradiation can be used in production of covalently modified enzymes.
Keywords: Conjugation; decolorization; gel permeation chromatography (GPC); microwave irradiation; peroxidase; reactive dye; ENZYME; STABILIZATION; PURIFICATION; CARRIER; Chemistry; Engineering